A single-dose antibiotic prophylaxis to prevent surgical site infection in clean-contaminated surgery among diabetic patients - Koirala, Kamal; Mukhia, Rupesh; Sharma, Suman; Manandhar, Sujan; Banepali, Niroj; Shrestha, Rishikesh Narayan; Khakurel, Mahesh; Raghubanshi, Bijendra Raj; Karki, Balman Singh (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Guidelines on antibiotics use in surgical patients recommends a single dose prophylaxis for clean-contaminated cases and therapeutic course for contaminated and dirty cases. Compliance to this guideline is poor among diabetic patients. The aim of this study was to test the efficacy of single dose antibiotic prophylaxis on the occurrence of postoperative surgical site infection (SSI) in clean-contaminated surgery in diabetic patients. Methods: Retrospective cross-sectional study was carried out at KIST Medical College and Teaching Hospital from September 2008 to August 2012 involving 144 diabetic patients who underwent major clean-contaminated surgery. Forty eight patients received one gram of ceftriaxone intravenously as prophylactic antibiotic within 30 minutes prior to incision (group 1) and 96 patients received three doses of ceftriaxone (group 2). One dose was given within 30 minutes prior to incision and other two doses were given postoperatively. All patients were followed up for 30 postoperative days on outpatient basis. The SSI rates were compared in two groups. Pus from the infected wound was tested for culture and sensitivity. Results: The SSI rates in group 1 and group 2 were of 5/48 (10.42%) and of 9/96 (9.37%) respectively. There was no significant difference in SSI rates between group 1 and group 2 (p=0.322). Conclusions: Single dose of Ceftriaxone shows the similar effect as three doses in clean-contaminated surgery in diabetic patients.